Physical characteristics and environmental risks assessment of oil-based drilling cuttings residues used for subgrade materials - Deming, Xiong; Chaoqiang, Wang (Journal of cleaner production, 2021)
Oil-based drilling cuttings residues (ODCRs) can be used as subgrade materials for well site construction. It not only reduces the cost of shale gas development, but also solves the practical problems encountered in shale gas development. The results show that ODCRs contained many carcinogenic pollutants, such as As, Benzo anthracene (a), Benzo pyrene (a), Dibenzo anthracene (a, h). ODCRs have some environmental risks. However, the main mineral components and radioactive strength of ODCRs meets the requirements of Class A materials, which can be used for building materials. The experimental results show that the unconfined compressive strength of ODCRs subgrade materials increases with the increase of cement content. The unconfined compressive strength and compactness first increase and then decrease with the increase of ODCRs content. The optimal content of cement is 4%, and the optimal content of ODCRs is 60%. In addition, ODCRs have pozzolanic characteristics. Active SiO2 and Al2O3 in ODCRs can react with Ca(OH)2 to produce a certain amount of gel materials, such as ettringite (AFt) and gel hydrated calcium silicate (C–S–H). These gel materials can form a network structure to encapsulate heavy metals and macromolecular organic matters. So, no organic pollutants and some heavy metals are detected in the leaching solution of subgrade materials with 60% ODCRs, and there will be no secondary pollution to the external environment.